Analisis Perbandingan Biaya Riil Dengan Tarif INA CBG Pasien Gangren Diabetik : ( Studi pada pasien rawat inap peserta JKN di Rumah Sakit Universitas Airlangga Surabaya) - Diajeng Putri Kinanti, - (2018)
Long-term uncontrolled hyperglycemia in patients with diabetes mellitus can cause damage to various body systems including nerve and blood vessel damage. Damage leads to disability and complications (IDF, 2017). One of the most common complications is diabetic gangrene. Hospitalization is a decision that must be made and therapy for diabetic gangrene requires many aspects that are observed and costly. Payment patterns are regulated in the INA CBG which is applied from the JKN system. This research is to find out the difference between the real cost and the INA CBG tariff and find out the factors that influence the real cost of diabetic gangrene patients hospitalized. Factors that influence are treatment class, length of treatment and severity level. The retrieval method was carried out retrospectively in diabetic gangrene patients hospitalized at Airlangga University Hospital Surabaya. Data were taken from medical record data, details of inpatient care costs, and claims data for diabetic gangrene patients. The perspective used is the perspective of the hospital. Data was obtained in total sampling with a period of 1 year, from January to December 2017. The results showed that there was a difference between the real cost and the INA CBG tariff (p = 0,000). The mean difference between the real cost and the INA CBG tariff is 169.581 ± 5.259.864,769. Based on the correlation test showed that there were significant correlations in the one factor, namely length of treatment (p = 0,009).